KOMODITAS PADI: TELAAH KEHILANGAN HASIL SAAT PANEN DI KABUPATEN JOMBANG - Syarif Imam Hidayat; Setyo Parsudi; Gerin Lingga Ayu Mustika Putri (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The research was conducted in Mojowarno District, Ngoro District and Peterongan District, Jombang Regency, from March to April 2020, in the rice field area. The aim of this research is to calculate the amount of yield loss and the value of the loss, to analyze the factors that influence the loss of yields, the efforts and strategic actions of farmers and the government to reduce yield losses. The missing results in this study include: harvesting, heaping, threshing, and drying activities. The research method used is descriptive quantitative method with the respondent determination technique using quota sampling of 75 people who are farmers in three sub-districts of Jombang Regency. The analysis technique used is the method of calculating the amount of loss and loss value (Riska, 2016), multiple linear regression, classical and descriptive assumption tests. The results of the study showed that the yield loss per hectare was 12.7% and the loss value was Rp.5,945,386.2, - Through the multiple linear regression method, it was found that there was a significant influence on land area, harvest age, farmer behavior, varieties, tools and the method of harvesting, thresher tools and the season for the loss of crop yields of 70.9% and the remaining 20.1% are other factors not examined. Strategic efforts that can be made for farmers are to use wholesale harvesting power, harvest on time, reduce threshing of grain at home, reduce the use of easy-to-fall rice varieties and reduce collection before threshing. For the government, this can be done by increasing the capacity and skills of farmers (capacity building), utilizing appropriate technology according to location, forming and empowering farmer groups.